Analysis Of Criminal Actions For Faking Rapid Test Letter As A Requirement For Traveling Out Of The City During The Covid-19 Pandemic - Sigar P. Berutu; Elvyn Frederychotan; Sri Juliani Br Simanungkalit; Dian Hardian Silalahi; Valentino Valentino (LEGAL BRIEF, 2023)
During the Covid-19 pandemic, it was found that the health certificates needed by many people for traveling outside the city as a requirement in preventing transmission of this virus were falsified. The crime of forging letters is a crime that is quite common in society during a pandemic. This study aims to examine the criminal act of forging a rapid test certificate as a condition for traveling out of town during the Covid-19 pandemic, against the background of the problem of how to regulate the criminal act of forging a medical certificate and the sanctions imposed on perpetrators of the crime of forging a rapid certificate. the Covid 19 test, and how law enforcement efforts to regulate the criminal act of falsifying medical certificates. The research method used in writing this thesis is descriptive, analysis leads to normative juridical, namely a material other law. This study uses library research techniques (Library Research). The analysis was carried out qualitatively. This research is an answer to the background of the problem related to the crime of forging a rapid test letter as a condition for traveling out of town during the Covid-19 pandemic. One form of law enforcement efforts to curb the criminal act of forging medical certificates is in one of the cases of forging rapid test certificates described in this study, in which the perpetrator was sentenced to 1 year and 10 months in prison by the Panel of Judges at the Pangkalan Bun District Court. The case above is a form of law enforcement against the act of making fake letters of the results of the Covid-19 rapid test.